2020
DOI: 10.1111/ppa.13198
|View full text |Cite
|
Sign up to set email alerts
|

Curvularia spicifera and Curvularia muehlenbeckiae causing leaf blight on Cunninghamia lanceolata

Abstract: Curvularia includes plant pathogenic species with a worldwide distribution and a wide host range, particularly cereals and grass (Poaceae). Chinese fir (Cunninghamia lanceolata) is an important afforestation tree species in southern China, with a high economic value. Leaf blight disease on Chinese fir was discovered in Hunan and Zhejiang, China, and two fungal species were found to be associated with the symptoms. Using morphological and phylogenetic approaches, they were identified as Curvularia spicifera and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, the presence of four Curvularia species in five out of 20 molecularly identified pathogens raises concern that Curvularia is an emerging threat to maize in India. C. sporobolicola was shown to be a pathogen of the grass Sporobolus australasicus in Australia [42] and C. siddiquii a pathogen of Pennisetum americanum in India [43], C. graminicola was isolated from Aristida ingrata (Poaceae) in Australia [44], and a taxonomically close relative of the fungus (Curvularia sp. BRIP 61674) was found to be a pathogen of Oryza spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of four Curvularia species in five out of 20 molecularly identified pathogens raises concern that Curvularia is an emerging threat to maize in India. C. sporobolicola was shown to be a pathogen of the grass Sporobolus australasicus in Australia [42] and C. siddiquii a pathogen of Pennisetum americanum in India [43], C. graminicola was isolated from Aristida ingrata (Poaceae) in Australia [44], and a taxonomically close relative of the fungus (Curvularia sp. BRIP 61674) was found to be a pathogen of Oryza spp.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The major fungal pathogens on Chinese fir include Colletotrichum fructicola Prihast., L capitalensis Henn., etc. [5][6][7][8][9][10][11] Among them, Colletotrichum spp. is one of the most widespread and destructive fungal pathogens in the cultivation areas of Chinese fir.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Candida , Solicoccozyma and Rhodotorula which play important role in the degradation of a variety of organic materials ( Shailubhai et al., 1985 ; Luo et al., 2021 ) showed higher abundance in the female papaya roots, suggesting that they could collaborate with endophytic bacteria to provide carbon nutrient for female papaya reproduction. However, in the roots of male papaya, some fungal species such as Gibellulopsis ( Giraldo and Crous, 2019 ) , Curvularia ( Cui et al, 2020 ), Colletotrichum ( Gautam, 2014 ) and Vishniacozyma ( Pem et al., 2020 ) which have been described as plant pathogens were enriched in male papaya. It has also been reported that some phytopathogens in the environment are of endophyte origins and that these innocuous fungal endophytes are beneficial to their host plants against the biotic and abiotic stresses through producing secondary metabolites, which is tigger by a long process of co-evolution ( Tan and Zou, 2001 ).…”
Section: Discussionmentioning
confidence: 99%